A production method for inhibiting martensitic transformation in 80 grade cord steel wire rod
By using medium-sized rectangular blanks combined with casting blank underpressure technology in the production of 80-level cord steel coils, combined with one-fire straight rolling, head rolling and cooling control processes, the problems of central segregation and martensite structure transformation of casting blanks are solved, and high-quality cord steel coils are produced and excellent drawing processing performance are achieved.
Patent Information
- Application Number
- CN202411835939.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-13
AI Technical Summary
During the production process of 80-level cord steel coils, improper process control leads to the center segregation of the casting billet and the transformation of the martensite structure, affecting the drawing processing performance.
The segregation and cooling speed of the casting blank are controlled by combining the casting blank underpressure process, and the formation of martensite structure is controlled through direct heat rolling, disengagement of the head rolling and unique post-rolling control process.
It effectively improves the segregation of the casting billet, reduces production costs, and suppresses the formation of martensite, so that the 80-level cord steel strips have good product quality and drawing processing performance.
Smart Images

Figure CN119307802B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cord steel wire rod production, and in particular to a production method for inhibiting martensitic transformation in a grade 80 cord steel wire rod. Background Art
[0002] Steel cord is a high-tech product among wire products. Not only is the production equipment expensive, but the production process is also very complicated. It is one of the products with the most stringent quality requirements among wire products. During the processing, the steel cord must undergo a series of deformations such as stretching, torsion and bending. During the service of the tire, it must withstand bending and stretching composite alternating loads and impact loads, so the quality of the raw wire rod plays a decisive role in the processing performance and use performance of the steel cord.
[0003] Martensite is a hard and brittle phase structure. It does not deform along with the matrix structure during the drawing process of the cord steel wire rod. As the drawing continues, cracks will initiate in front and behind the martensite and continue to expand, eventually leading to wire breakage. Therefore, martensite is a structure that must be eliminated in the cord steel wire rod.
[0004] When producing high-strength steel cord or some ultra-high-strength steel cord, 80-grade cord steel wire rod is used. Due to insufficient tooling conditions or improper process control, the ingot will have serious center segregation. Since there is a serious segregation of C and Mn elements in the center segregation area, and their content far exceeds the average composition of the matrix, in order to avoid the precipitation of center network carbon in this area after rolling, a strong cooling process is generally used, but it brings the risk of martensitic transformation, which seriously affects the drawing processing performance.
[0005] At present, the industry uses two process flows to produce this wire rod, one is the small square billet process flow, and the other is the large square billet process flow. When using small square billet continuous casting, due to the small billet shape, even with electromagnetic stirring and billet pressing technology, it is still impossible to ensure the low segregation and stability of the billet, resulting in the center segregation of the wire rod after rolling, and the network cementite and martensite are in a large fluctuation state, which cannot meet the high compression rate deformation of the steel cord processing process. It is very easy to break by drawing or stranding, and the wire fracture mostly shows a central burr state, which has a great impact on the yield rate and processing cost of the steel cord. Using large square billet continuous casting, the continuous casting weak cold combined with the billet pressing process can have a good improvement on the center segregation of the billet, but the large square billet must be heated and rolled twice to obtain the required specifications of the cord steel wire rod. The process is long, the cost is high, the economy is poor, and it is not competitive in the market. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a production method for inhibiting the martensitic transformation in 80-grade cord steel wire rod, which adopts a medium-sized rectangular billet combined with a casting billet reduction process, and adopts a single-fire direct rolling, head-off rolling and a unique post-rolling controlled cooling process, which can not only improve the segregation of the casting billet and avoid the increase in production costs, but also inhibit the formation of martensitic structure, so that the 80-grade cord steel wire rod has good product quality and drawing processing performance.
[0007] Based on the above purpose, the present invention provides a production method for inhibiting martensitic transformation in 80-grade cord steel wire rod, comprising the following steps: molten iron pretreatment → converter smelting → LF refining → continuous casting → heating → controlled rolling → controlled cooling; the continuous casting process adopts electromagnetic stirring combined with the heavy pressure reduction process of the cast billet, and the total reduction under heavy pressure is controlled to reach 9-11%, and the carbon segregation index of the continuous casting billet is 0.98-1.08; the controlled rolling adopts a head-off billet opening machine added before the rough rolling mill, first rolling the cast billet into an intermediate billet, and then entering the one-fire direct rolling process of the rough rolling mill; in the controlled cooling process, the cooling rates before, during and after the phase change are controlled to be 20-25℃ / s, 3-8℃ / s, and ≤3℃ / s, respectively.
[0008] During the continuous casting process, the continuous casting speed is controlled at 1.25-1.35m / min, and the superheat is controlled at 15-25℃; the current of the crystallizer electromagnetic stirring is 580-620A, the frequency is 2-4Hz, and the current of the end electromagnetic stirring is 490-510A, the frequency is 11-13Hz; the secondary cooling adopts a weak cooling process, and the specific water volume is controlled at 0.25-0.30L / kg; the area of the equiaxed crystal area of the billet accounts for 65-75%, and the central shrinkage cavity is 0-0.5 level. The billet passes through 10 sets of tension and correction rollers, and the total reduction under heavy pressure reaches 9-11%. The reduction passes and reductions are 0 / 0 / 0 / 3 / 3 / 3 / 4 / 5 / 0 / 0mm and 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm respectively. After heavy pressure, the size of the billet is 182×244-178×246mm. The low-power inspection of the ingot shows no middle cracks. The continuous casting process uses electromagnetic stirring of the crystallizer, electromagnetic stirring at the end of solidification and heavy pressure reduction technology to produce medium-sized rectangular ingots. Through low superheat control, secondary cooling and weak cooling process and appropriate pulling speed control, it can prevent the generation of middle cracks during the pulling and straightening of the ingot, and homogenize the chemical composition of the central mushy area, maximize the dispersion and shrinkage of the central molten steel, avoid the formation of central shrinkage holes and central component segregation areas, and create good matrix conditions for wire rod organization control.
[0009] During the controlled rolling process, the descaling pressure is controlled to be ≥20MPa, and 4 headless blanking machines are added before the rough rolling mill. The starting rolling temperature is 1020-1120℃, the finishing rolling temperature is 900-930℃, and the sizing temperature is 900-930℃. A high-power descaling machine is used in the rolling process to increase the descaling water pressure to more than 20MPa, which can remove the iron oxide scale on the surface of the steel billet and avoid surface defects caused by the pressing of iron oxide scale on the surface of the rolled piece and the finished product. Due to the large billet shape, in order to reduce the cost of the rolling process, a one-fire direct rolling technology is adopted, that is, 4 headless blanking machines are added before the traditional rough rolling mill, and the 182×244-178×246 rectangular billets are rolled into 160×160mm intermediate billets, and then enter the traditional rough rolling unit.
[0010] During the controlled cooling process, the wire rod spinning temperature is controlled at 915-945°C, the initial roller speed is 1.10m / s, and the rated air volume of the fan is 280000m 3 / h, the air volume of the first 4 fans is 75% of the rated air volume of the fan, the air volume of the 5th fan is 65% of the rated air volume of the fan, the air volume of the 6th fan is 50% of the rated air volume of the fan, the air volume of the 7th-8th fan is 40% of the rated air volume of the fan, and the remaining fans are turned off. When the temperature of the wire rod drops below 580℃, a heat preservation cover is added. The post-rolling controlled cooling process adopts an axial flow high-wind secret exhaust arrangement, combined with the adjustment of the Jialing device, the roller speed and the fan air volume setting, to increase the cooling rate before the phase transformation after the wire rod is spun, and inhibit the precipitation of the network pro-eutectoid cementite; reduce the cooling rate during and after the phase transformation, and inhibit the formation of martensite; when the temperature of the wire rod drops below 580℃, a heat preservation cover is added to fully release the phase transformation stress and shorten the natural aging period. During the controlled cooling process, the cooling rates before, during and after the phase transformation are controlled to be 20-25℃ / s, 3-8℃ / s, and ≤3℃ / s, respectively.
[0011] The molten iron pretreatment uses molten iron and undergoes a pre-desulfurization process to control S≤0.005% and Ti≤0.03% in the molten iron entering the furnace. The converter uses a double slag process to control P≤0.008%. All scrap steel uses self-produced clean scrap steel to control the addition of harmful elements and residual elements.
[0012] The converter smelting adopts a high carbon drawing method to control the steel output C≥0.15%, O≤0.050%, P≤0.008%, and S≤0.010%.
[0013] The double slag method is used in the LF refining process to promote the plasticization of inclusions. The first slag making controls the slag basicity to 2.5-3.0; the second slag making controls the slag basicity to 0.7-0.9; the argon flow rate during soft blowing is 55-58L / min, and the soft blowing time is ≥60min. The refining process uses magnesium-carbon refractory materials and low-aluminum and low-titanium alloy auxiliary materials to reduce the generation of alumina inclusions and titanium inclusions. Long-term soft blowing is used to fully stir the molten steel to allow the inclusions to aggregate, grow, float and be removed. At the same time, the double slag method is used to promote the plasticization of inclusions, so that the inclusions in the wire rod extend as the matrix deforms during hot rolling and cold drawing, thereby improving the deep drawing performance of the wire rod and reducing the risk of wire breakage during drawing.
[0014] The temperature of the second heating section used in the heating is 950-1080° C., and the temperature of the soaking section is 1060-1160° C. It is ensured that the heating time of the second heating section and the soaking section is not less than 100 minutes, the furnace pressure is not less than 15 Pa, and the residual oxygen content is 0.5-2.0%.
[0015] The chemical composition of the 80-grade cord steel wire rod includes, by mass percentage, C: 0.80-0.85%, Si: 0.25-0.30%, Mn: 0.40-0.45%, S≤0.008%, P≤0.010%, Al≤0.002%, Ti≤0.001%, O≤0.0015%, N≤0.0035%, and the rest are Fe and unavoidable impurity elements.
[0016] Beneficial effects of the present invention: the martensitic structure of the 80-grade cord steel wire rod produced by the present invention is grade 0, the proportion of central segregation ≤ grade 1 reaches 100%, the proportion of grain boundary cementite ≤ grade 1 reaches 100%, the depth of the full decarburization layer is 0, the total decarburization layer depth is ≤30μm, the proportion of troostite is ≥80%, the depth of surface defects and iron oxide scale indentation is ≤0.03mm, the purity of wire rod inclusions is ≤0.02%, and the tensile strength difference is ≤40MPa. After actual production of φ0.30mm ultra-high strength steel cord, the wet wire breakage rate is less than 0.8 times / ton, and the wire breakage rate of twisted strands is less than 2 times / ton, which is better than the actual quality level of the benchmark supplier. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is a schematic diagram of the metallographic structure of Example 1 of the present invention, in which no martensite is found;
[0019] Figure 2Schematic diagram of the metallographic structure of Comparative Example 1, in which level 3 martensite is found;
[0020] Figure 3 Schematic diagram of wire rod segregation in Example 1 of the present invention, where the center segregation is level 0;
[0021] Figure 4 It is a schematic diagram of wire rod segregation of comparative example 1, and the center segregation is level 1.5. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should have the common meanings understood by persons having ordinary skills in the field to which the present invention belongs.
[0024] The present invention uses molten iron and undergoes a pre-desulfurization process, and the converter uses self-produced clean scrap steel to reduce harmful elements in the steel; through smelting control, slag blocking steel tapping, excess steel operation and refractory and alloy auxiliary materials, combined with inclusion plasticization technology to improve the purity of molten steel; the continuous casting process uses electromagnetic stirring combined with medium-sized billet heavy pressure reduction technology, combined with one-fire direct rolling technology, head-off rolling technology and precise control of cooling speed before, during and after phase transformation to suppress the generation of center network carbon and martensite, thereby obtaining 80-grade cord steel wire rod with excellent deep drawing performance. The present invention is described in detail in conjunction with embodiments below. Example 1
[0025] Chemical composition of wire rod: by mass percentage, C: 0.83%, Si: 0.26%, Mn: 0.42%, S: 0.006%, P: 0.009%, Al: 0.0014%, Ti: 0.0005%, O: 0.0011%, N: 0.0022%, and the rest are Fe and unavoidable impurity elements.
[0026] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.004% and the Ti content is 0.025%.
[0027] Converter smelting: All scrap steel is self-produced clean scrap steel, with 35 tons added. High carbon drawing technology is used, and the steel output is C: 0.18%, O: 0.043%, P: 0.007%, S: 0.004%.
[0028] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. The double slag method is used to promote the plasticization of inclusions. The basicity of high basicity slag is 2.7, and the basicity of low basicity slag is 0.85; the argon flow rate during soft blowing is 57L / min, and the soft blowing time is 64min.
[0029] Continuous casting: The continuous casting process adopts the technology of electromagnetic stirring of the crystallizer, electromagnetic stirring at the end of solidification and heavy pressure reduction. The internal size of the crystallizer copper tube is a 200mm×240mm rectangular billet section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.30m / min, and the superheat is 18-22℃; the crystallizer electromagnetic stirring current is 600A, the frequency is 3Hz, and the end electromagnetic stirring current is 500A, and the frequency is 12Hz. The secondary cooling adopts a weak cooling process, and the specific water volume is 0.28L / kg. The billet passes through 10 sets of tension and correction rollers, and the total pressure reduction under heavy pressure reaches 11%. The pressure reduction passes and pressure reduction are 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm respectively. After heavy pressure reduction, the size of the billet is 178×246mm. After low-power inspection of the billet, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 72%, and the central shrinkage cavity is level 0. The carbon segregation index of the continuous casting billet is 1.06 by drilling method.
[0030] Heating: The temperature of the second heating section of the walking beam heating furnace is 1054-1075°C, the temperature of the soaking section is 1097-1122°C, the heating time of the second heating section and the soaking section is 123 minutes in total, the furnace pressure is 16-23Pa, and the residual oxygen content is 0.8-1.7%.
[0031] Rolling: After heating, the steel billet is descaled by high-pressure water to remove the surface oxide scale, and the descaling pressure is 21MPa. The descaled 178×246mm rectangular billet is rolled into 160×160mm intermediate billet by 4 headless billet opening mills, and then enters the traditional rough rolling unit. The starting rolling temperature is 1032~1064℃, the finishing rolling temperature is 912-926℃, and the sizing temperature is 915-928℃.
[0032] Controlled cooling: spinning temperature 918-932℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, the air volumes of fans 1-8 were 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the other fans were turned off. The temperature of the wire rod entering the 12th insulation cover was 563℃. The average cooling rates before, during and after the phase change were 22.8℃ / s, 5.5℃ / s and 2.8℃ / s respectively.
[0033] Inspection results: 100% of the wire rod martensite structure is grade 0, 100% of the center segregation is grade 0-1, 100% of the grain boundary cementite is grade 0-1, the depth of the full decarburization layer is 0, the total decarburization layer depth is 20-35μm, the proportion of sorbite is 85%, the depth of surface defects and iron oxide scale is 0-0.03mm, the purity of wire rod inclusions is 0.006%, and the tensile strength difference is 28MPa. After producing φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing is 0.7 times / ton, and the total broken wire rate of twisting is 1.8 times / ton. Example 2
[0034] Chemical composition of wire rod: by mass percentage, C: 0.81%, Si: 0.27%, Mn: 0.43%, S: 0.005%, P: 0.010%, Al: 0.0008%, Ti: 0.0004%, O: 0.0009%, N: 0.0023%, and the rest are Fe and unavoidable impurity elements.
[0035] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.005% and the Ti content is 0.022%.
[0036] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons added. High carbon drawing technology is used, and the steel output is C: 0.16%, O: 0.047%, P: 0.009%, S: 0.006%.
[0037] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. The double slag method is used to promote the plasticization of inclusions. The basicity of high basicity slag is 2.6, and the basicity of low basicity slag is 0.9; the argon flow rate during soft blowing is 66L / min, and the soft blowing time is 58min.
[0038] Continuous casting: The continuous casting process adopts the technology of electromagnetic stirring of the crystallizer, electromagnetic stirring at the end of solidification and heavy pressure reduction. The internal size of the crystallizer copper tube is a 200mm×240mm rectangular billet section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.30m / min, and the superheat is 19-24℃; the crystallizer electromagnetic stirring current is 600A, the frequency is 3Hz, and the end electromagnetic stirring current is 500A, and the frequency is 12Hz. The secondary cooling adopts a weak cooling process, and the specific water volume is 0.28L / kg. The billet passes through 10 sets of tension and correction rollers, and the total reduction under heavy pressure reaches 11%. The number of reduction passes and the reduction are 0 / 0 / 0 / 3 / 3 / 3 / 4 / 5 / 0 / 0mm respectively. After heavy pressure, the size of the billet is 182×244mm. After low-power inspection of the billet, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 70%, and the central shrinkage cavity is level 0. The carbon segregation index of the continuous casting billet is 1.04 by drilling method.
[0039] Heating: The temperature of the second heating section of the walking beam heating furnace is 1032-1061°C, the temperature of the soaking section is 1086-1115°C, the heating time of the second heating section and the soaking section is 126 minutes in total, the furnace pressure is 18-25Pa, and the residual oxygen content is 0.6-1.9%.
[0040] Rolling: After heating, the steel billet is descaled by high-pressure water to remove the surface iron oxide scale, and the descaling pressure is 21MPa. The descaled 182×244mm rectangular billet is rolled into 160×160mm intermediate billet by 4 headless billet opening mills, and then enters the traditional rough rolling unit. The starting rolling temperature is 1022~1055℃, the finishing rolling temperature is 907-921℃, and the sizing temperature is 913-928℃.
[0041] Controlled cooling: spinning temperature 920-937℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, the air volume of fans 1-8# was 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the other fans were turned off. The temperature of the wire rod entering the 12th insulation cover was 571℃. The average cooling rates before, during and after the phase change were 23.2℃ / s, 4.6℃ / s and 2.4℃ / s respectively.
[0042] Inspection results: 100% of the wire rod martensite structure is grade 0, 100% of the center segregation is grade 0-1, 100% of the grain boundary cementite is grade 0-1, the depth of the full decarburization layer is 0, the total decarburization layer depth is 20-30μm, the proportion of sorbite is 85%, the depth of surface defects and iron oxide scale is 0-0.03mm, the purity of wire rod inclusions is 0.009%, and the tensile strength difference is 36MPa. After producing φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing is 0.6 times / ton, and the total broken wire rate of twisting is 1.7 times / ton. Example 3
[0043] Chemical composition of wire rod: by mass percentage, C: 0.82%, Si: 0.26%, Mn: 0.44%, S: 0.007%, P: 0.008%, Al: 0.0011%, Ti: 0.0006%, O: 0.0012%, N: 0.0021%, and the rest are Fe and unavoidable impurity elements.
[0044] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.004% and the Ti content is 0.020%.
[0045] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons added. High carbon drawing technology is used, and the steel output is C: 0.21%, O: 0.035%, P: 0.008%, S: 0.007%.
[0046] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. The double slag method is used to promote the plasticization of inclusions. The basicity of high basicity slag is 2.8, and the basicity of low basicity slag is 0.8; the argon flow rate during soft blowing is 58L / min, and the soft blowing time is 65min.
[0047] Continuous casting: The continuous casting process adopts electromagnetic stirring of the crystallizer, electromagnetic stirring at the end of solidification and heavy pressure reduction technology. The internal size of the crystallizer copper tube is a 200mm×240mm rectangular billet section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.30m / min, and the superheat is 17-23℃; the crystallizer electromagnetic stirring current is 600A, the frequency is 3Hz, and the end electromagnetic stirring current is 500A, and the frequency is 12Hz. The secondary cooling adopts a weak cooling process, and the specific water volume is 0.28L / kg. The billet passes through 10 sets of tension and correction rollers, and the total reduction under heavy pressure reaches 11%. The number of reduction passes and the reduction are 0 / 0 / 0 / 3 / 4 / 4 / 5 / 6 / 0 / 0mm respectively. After heavy pressure, the size of the billet is 178×246mm. After low-power inspection of the billet, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 71%, and the central shrinkage cavity is level 0. The carbon segregation index of the continuous casting billet is 1.05 by drilling method.
[0048] Heating: The temperature of the second heating section of the walking beam heating furnace is 1010-1051°C, the temperature of the soaking section is 1066-1128°C, the heating time of the second heating section and the soaking section is 118 minutes in total, the furnace pressure is 21-29Pa, and the residual oxygen content is 0.7-1.8%.
[0049] Rolling: After heating, the steel billet is descaled by high-pressure water to remove the surface oxide scale, and the descaling pressure is 21MPa. The descaled 178×246mm rectangular billet is rolled into 160×160mm intermediate billet by 4 headless billet opening mills, and then enters the traditional rough rolling unit. The starting rolling temperature is 1038~1065℃, the finishing rolling temperature is 904-922℃, and the sizing temperature is 910-925℃.
[0050] Controlled cooling: spinning temperature 918-939℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, the air volume of fans 1-8 was 75% / 75% / 75% / 75% / 65% / 50% / 40% / 40% respectively, and the other fans were turned off. The temperature of the wire rod entering the 12th insulation cover was 561℃. The average cooling rates before, during and after the phase change were 24.2℃ / s, 6.4℃ / s and 2.3℃ / s respectively.
[0051] Inspection results: 100% of the wire rod martensite structure is grade 0, 100% of the center segregation is grade 0-1, 100% of the grain boundary cementite is grade 0-1, the depth of the full decarburization layer is 0, the total decarburization layer depth is 20-30μm, the proportion of sorbite is 85%, the depth of surface defects and iron oxide scale is 0-0.03mm, the purity of wire rod inclusions is 0.011%, and the tensile strength difference is 35MPa. After producing φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing is 0.7 times / ton, and the total broken wire rate of twisting is 1.7 times / ton.
[0052] Comparative Example 1:
[0053] Chemical composition of wire rod: by mass percentage, C: 0.81%, Si: 0.27%, Mn: 0.43%, S: 0.007%, P: 0.009%, Al: 0.0018%, Ti: 0.0008%, O: 0.0014%, N: 0.0029%, and the rest are Fe and unavoidable impurity elements.
[0054] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.004% and the Ti content is 0.027%.
[0055] Converter smelting: All scrap steel is self-produced clean scrap steel, with 34 tons added. High carbon drawing technology is used, and the steel output is C: 0.17%, O: 0.045%, P: 0.009%, S: 0.008%.
[0056] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. Low basicity slag is used to promote plasticization of inclusions, with a basicity of 0.8; the argon flow rate during soft blowing is 58L / min, and the soft blowing time is 34min.
[0057] Continuous casting: The continuous casting process uses electromagnetic stirring of the crystallizer and electromagnetic stirring at the end of solidification. The internal dimensions of the crystallizer copper tube are 160mm×160mm in section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.80m / min, and the superheat is 21-28℃; the crystallizer electromagnetic stirring current is 300A, the frequency is 3.5Hz, and the end electromagnetic stirring current is 500A, and the frequency is 10Hz. The secondary cooling adopts a strong cooling process with a specific water volume of 1.28L / kg. After low-power inspection of the ingot, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 58%, and the central shrinkage cavity is 1.0. The carbon segregation index of the continuous casting ingot is 1.18 using the drilling method.
[0058] Heating: The temperature of the second heating section of the walking beam heating furnace is 970-1064°C, the temperature of the soaking section is 1066-1120°C, the heating time of the second heating section and the soaking section is 66 minutes in total, the furnace pressure is 12-27Pa, and the residual oxygen content is 0.9-3.5%.
[0059] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1018-1074℃, the finishing rolling temperature is 902-923℃, and the sizing temperature is 908-919℃.
[0060] Controlled cooling: spinning temperature 887-909℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, the air volumes of fans 1-9# were 75% / 75% / 75% / 75% / 65% / 65% / 60% / 50% / 40% respectively, the other fans were turned off, and the insulation covers were all opened. The average cooling rates before, during and after the phase change were 23.2℃ / s, 10.3℃ / s and 5.3℃ / s respectively.
[0061] Inspection results: Wire rod martensite structure of level 0 accounts for 95%, level 1-3 accounts for 5%; center segregation of level 0-1 accounts for 80%, level 1.5-2.0 accounts for 20%; grain boundary cementite of level 0-1 accounts for 90%, level 2-3 accounts for 10%; full decarburization layer depth is 0, total decarburization layer depth is 20-30μm, sorbite proportion is 85%, surface defects and iron oxide scale indentation depth is 0-0.05mm, wire rod inclusion purity is 0.025%, tensile strength difference is 45MPa. After the customer produced φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing was 1.3 times / ton, and the total broken wire rate of twisted strands was 4.2 times / ton.
[0062] Comparative Example 2:
[0063] Chemical composition of wire rod: by mass percentage, C: 0.83%, Si: 0.28%, Mn: 0.42%, S: 0.008%, P: 0.010%, Al: 0.0016%, Ti: 0.0009%, O: 0.0012%, N: 0.0027%, and the rest are Fe and unavoidable impurity elements.
[0064] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.005% and the Ti content is 0.024%.
[0065] Converter smelting: All scrap steel is self-produced clean scrap steel, with 32 tons added. High carbon drawing technology is used, and the steel output is C: 0.16%, O: 0.044%, P: 0.008%, S: 0.009%.
[0066] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. Low basicity slag is used to promote plasticization of inclusions, with a basicity of 0.9; the argon flow rate during soft blowing is 59L / min, and the soft blowing time is 38min.
[0067] Continuous casting: The continuous casting process uses electromagnetic stirring of the crystallizer and electromagnetic stirring at the end of solidification. The internal size of the crystallizer copper tube is 160mm×160mm in section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.80m / min, and the superheat is 22-27℃; the crystallizer electromagnetic stirring current is 300A, the frequency is 3.5Hz, and the end electromagnetic stirring current is 500A, and the frequency is 10Hz. The secondary cooling adopts a strong cooling process with a specific water volume of 1.28L / kg. After low-power inspection of the ingot, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 61%, and the central shrinkage cavity is 1.0-1.5. The carbon segregation index of the continuous casting ingot is 1.23 using the drilling method.
[0068] Heating: The temperature of the second heating section of the walking beam heating furnace is 980-1052°C, the temperature of the soaking section is 1071-1135°C, the heating time of the second heating section and the soaking section is 68 minutes in total, the furnace pressure is 10-35Pa, and the residual oxygen content is 1.0-4.8%.
[0069] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1010-1064℃, the finishing rolling temperature is 905-921℃, and the sizing temperature is 907-918℃.
[0070] Controlled cooling: spinning temperature 885-919℃, initial roller speed 1.10m / s, fan air volume 280000m3 / h, 1-9# fan air volumes 75% / 75% / 75% / 75% / 65% / 65% / 60% / 50% / 40% respectively, other fans are turned off, and all insulation covers are opened. The average cooling rates before, during and after phase change are 21.4℃ / s, 9.8℃ / s and 4.6℃ / s respectively.
[0071] Inspection results: Wire rod martensite structure of level 0 accounts for 95%, 1-3 accounts for 5%; center segregation of level 0-1 accounts for 75%, 1.5-2.0 accounts for 25%; grain boundary cementite of level 0-1 accounts for 85%, 2-3 accounts for 15%; full decarburization layer depth is 0, total decarburization layer depth is 10-30μm, sorbite proportion is 85%, surface defects and iron oxide scale indentation depth is 0-0.04mm, wire rod inclusion purity is 0.034%, tensile strength difference is 40MPa. After the customer produced φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing was 1.5 times / ton, and the total broken wire rate of twisted strands was 4.8 times / ton.
[0072] Comparative Example 3:
[0073] Chemical composition of wire rod: by mass percentage, C: 0.82%, Si: 0.26%, Mn: 0.43%, S: 0.008%, P: 0.009%, Al: 0.0018%, Ti: 0.0007%, O: 0.0014%, N: 0.0032%, and the rest are Fe and unavoidable impurity elements.
[0074] Hot metal pretreatment: Hot metal is used and pre-desulfurized, and the S content of the hot metal entering the furnace is 0.004% and the Ti content is 0.028%.
[0075] Converter smelting: All scrap steel is self-produced clean scrap steel, with 33 tons added. High carbon drawing technology is used, and the steel output is C: 0.18%, O: 0.038%, P: 0.009%, S: 0.006%.
[0076] Refining: LF refining uses magnesium carbon refractory and low aluminum and low titanium alloy auxiliary materials to reduce alumina inclusions and titanium inclusions. Low basicity slag is used to promote plasticization of inclusions, with a basicity of 0.9; the argon flow rate during soft blowing is 56L / min, and the soft blowing time is 42min.
[0077] Continuous casting: The continuous casting process uses electromagnetic stirring of the crystallizer and electromagnetic stirring at the end of solidification. The internal size of the crystallizer copper tube is 160mm×160mm in section, and an integral water nozzle is used for pouring. The continuous casting speed is 1.80m / min, and the superheat is 24-29℃; the crystallizer electromagnetic stirring current is 300A, the frequency is 3.5Hz, and the end electromagnetic stirring current is 500A, and the frequency is 10Hz. The secondary cooling adopts a strong cooling process, and the specific water volume is 1.28L / kg. After low-power inspection of the ingot, there is no intermediate crack, the area of the equiaxed crystal zone accounts for 63%, and the central shrinkage cavity is 1.0-1.5. The carbon segregation index of the continuous casting ingot is 1.21 by drilling method.
[0078] Heating: The temperature of the second heating section of the walking beam heating furnace is 974-1043°C, the temperature of the soaking section is 1077-1148°C, the heating time of the second heating section and the soaking section is 65 minutes in total, the furnace pressure is 8-32Pa, and the residual oxygen content is 0.9-4.5%.
[0079] Rolling: After heating, the steel billet is descaled by high-pressure water to remove surface oxide scale. The descaling pressure is 12MPa, the starting rolling temperature is 1026-1072℃, the finishing rolling temperature is 903-926℃, and the sizing temperature is 907-924℃.
[0080] Controlled cooling: spinning temperature 889-917℃, roller initial speed 1.10m / s, fan air volume 280000m 3 / h, the air volumes of fans 1-9# were 75% / 75% / 75% / 75% / 65% / 65% / 60% / 50% / 40% respectively, the other fans were turned off, and the insulation covers were all opened. The average cooling rates before, during and after the phase change were 22.8℃ / s, 8.7℃ / s and 5.6℃ / s respectively.
[0081] Inspection results: Wire rod martensite structure of level 0 accounts for 95%, 1-3 accounts for 5%; center segregation of level 0-1 accounts for 80%, 1.5-2.0 accounts for 20%; grain boundary cementite of level 0-1 accounts for 90%, 2-3 accounts for 10%; full decarburization layer depth is 0, total decarburization layer depth is 10-30μm, sorbite proportion is 85%, surface defects and iron oxide scale indentation depth is 0-0.04mm, wire rod inclusion purity is 0.031%, tensile strength difference is 40MPa. The customer produced φ0.30mm ultra-high strength steel cord, the total broken wire rate of wet drawing is 1.4 times / ton, and the total broken wire rate of twisting is 3.8 times / ton.
[0082] The test results of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 below.
[0083]
[0084] Those skilled in the art should understand that the discussion of any of the above embodiments is only exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A production method for inhibiting martensitic transformation in a grade 80 cord steel wire rod, characterized in that: The method comprises the following steps: molten iron pretreatment → converter smelting → LF refining → continuous casting → heating → controlled rolling → controlled cooling; the continuous casting process adopts electromagnetic stirring combined with the heavy pressure reduction process of the cast billet, and the total reduction under heavy pressure is controlled to reach 9-11%, and the carbon segregation index of the continuous casting billet is 0.98-1.08; the controlled rolling adopts a head-off billet opening machine added before the rough rolling mill, and the billet is first rolled into an intermediate billet, and then enters the one-fire direct rolling process of the rough rolling mill; in the controlled cooling process, the cooling rates before, during and after the phase change are controlled to be 20-25℃ / s, 3-8℃ / s and ≤3℃ / s respectively; The chemical composition of the 80-grade cord steel wire rod includes, by mass percentage, C: 0.80-0.85%, Si: 0.25-0.30%, Mn: 0.40-0.45%, S≤0.008%, P≤0.010%, Al≤0.002%, Ti≤0.001%, O≤0.0015%, N≤0.0035%, and the rest are Fe and unavoidable impurity elements.
2. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: During the continuous casting process, the continuous casting speed is controlled at 1.25-1.35m / min, and the superheat is controlled at 15-25°C; the current of the electromagnetic stirring of the crystallizer is 580-620A, the frequency is 2-4Hz, the current of the terminal electromagnetic stirring is 490-510A, and the frequency is 11-13Hz; the secondary cooling adopts a weak cooling process, and the specific water volume is controlled at 0.25-0.30L / kg; the area of the equiaxed crystal zone of the ingot accounts for 65-75%, and the central shrinkage cavity is level 0-0.
5.
3. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: In the controlled rolling process, the descaling pressure is controlled to be ≥20MPa, 4 head-dropping slab opening machines are added before the rough rolling mill, the starting rolling temperature is 1020-1120°C, the finishing rolling temperature is 900-930°C, and the sizing temperature is 900-930°C.
4. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 3, characterized in that: After heavy pressing, the size of the cast billet is a rectangular billet of 182×244-178×246mm. During the controlled rolling process, 4 headless billet opening machines are used to roll the 182×244-178×246mm rectangular billet into an intermediate billet of 160×160mm, and then the billet enters the rough rolling unit for rolling.
5. The method for suppressing martensitic transformation in grade 80 cord steel wire rod according to claim 1, characterized in that: During the controlled cooling process, the wire rod spinning temperature is controlled at 915-945°C, the initial roller speed is 1.10m / s, and the rated air volume of the fan is 280000m 3 / h, the air volume of the first 4 fans is 75% of the rated air volume of the fan, the air volume of the 5th fan is 65% of the rated air volume of the fan, the air volume of the 6th fan is 50% of the rated air volume of the fan, the air volume of the 7th-8th fans is 40% of the rated air volume of the fan, and the remaining fans are turned off. When the wire rod temperature drops below 580℃, the thermal insulation cover is added.
6. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The molten iron pretreatment adopts molten iron and undergoes a pre-desulfurization process to control S≤0.005% and Ti≤0.03% in the molten iron entering the furnace.
7. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The converter smelting adopts a high carbon drawing method to control the steel output C≥0.15%, O≤0.050%, P≤0.008%, and S≤0.010%.
8. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: In the LF refining process, a double slag method is used to promote plasticization of inclusions. The first slag making controls the slag basicity to be 2.5-3.0; the second slag making controls the slag basicity to be 0.7-0.9; the argon flow rate during soft blowing is 55-58 L / min, and the soft blowing time is ≥60 min.
9. The method for suppressing martensitic transformation in a grade 80 cord steel wire rod according to claim 1, characterized in that: The temperature of the second heating section used in the heating is 950-1080°C, and the temperature of the soaking section is 1060-1160°C.
Citation Information
Patent Citations
Method for controlling network cementites in ultrahigh-carbon steel wire cord
CN105256119A
80-grade tire cord steel wire rod being suitable for acidic-pickling descaling and production method of same
CN105316573A